2014
DOI: 10.1186/1478-4505-12-68
|View full text |Cite
|
Sign up to set email alerts
|

Needs assessment to strengthen capacity in water and sanitation research in Africa: experiences of the African SNOWS consortium

Abstract: BackgroundDespite its contribution to global disease burden, diarrhoeal disease is still a relatively neglected area for research funding, especially in low-income country settings. The SNOWS consortium (Scientists Networked for Outcomes from Water and Sanitation) is funded by the Wellcome Trust under an initiative to build the necessary research skills in Africa. This paper focuses on the research training needs of the consortium as identified during the first three years of the project.MethodsWe reviewed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The need to better support researchers with post-award tasks was frequently cited. 6,7,[29][30][31][32][33] This stems from reports of significant workloads, a stressful environment in HEIs and issues in communications and working relationships.…”
Section: Supporting Researchers With Tasksmentioning
confidence: 99%
See 2 more Smart Citations
“…The need to better support researchers with post-award tasks was frequently cited. 6,7,[29][30][31][32][33] This stems from reports of significant workloads, a stressful environment in HEIs and issues in communications and working relationships.…”
Section: Supporting Researchers With Tasksmentioning
confidence: 99%
“…63,64 However, we found that specific responsibilities for requirements, and the level of support offered to researchers in HEIs, depends on availability of research management and administrative (RMA) infrastructure (such as availability of RAs) and other factors in institutional set up. 6,7,[29][30][31][32]65 As such, while certain award tasks, such as negotiation of contracts and hiring, can be delegated to relevant HEI departments (such as Human Resources and Finance) the level of support offered for other activitiessuch as review and approval of research operations, managing direct information requests and reportingis not always clear due to differences in HEI facilities, resources, and internal funding. In addition, RMA appears to heavily vary by country, [65][66][67] and even where it is readily available (such as in dedicated 'grant offices' or 'post-award offices' 3 ) a 'systematic problem' of administrative burden and issues with compliance is still being reported, 68 with issues stemming from factors such as overburdened central offices, 31 poor leadership, 42 inadequate training, 30,65 and ineffective relationships between researchers and administrators.…”
Section: Implications Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Barriers to this, such as poor funding and lack of protected time for research pursuits, have been a common complaint from African researchers [25], which is why the Research Fellows scheme was a key success of the SHARE programme. Investing in postgraduate and doctoral studies in phases I and II was also an important achievement of the SHARE programme, as the need to provide more support for postgraduate training in health sciences in African universities is globally recognised [26, 27] if we are to increase the capacity of institutions. In both phases, locally driven research agendas were a priority.…”
Section: Main Textmentioning
confidence: 99%
“…Indeed, in the Introduction to the Call for Papers, the importance of capacity building is highlighted. This, too, is a topic described in recent papers in HARPS , such as those by Ager and Zarowsky [ 19 ], analysing the experiences of the Health Research Capacity Strengthening initiative’s Global Learning program of work across sub-Saharan Africa, and by Hunter et al [ 20 ], describing needs assessment to strengthen capacity in water and sanitation research in Africa.…”
Section: Editorialmentioning
confidence: 99%